The impact of adolescent marriage on child stunting: Socio-cultural dynamics and policy implications in rural communities - Basir; Aril, Sahrul; Nasaruddin, Nasywa Salsabila; Meilidya, Aliyah; Setiawan, Risdya Devina Ayu; Rahman, Nur Rahma; Rini; Ramadhani, A. Filsa Salzabila (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Early marriage often involves partners who are socially and emotionally immature, leading to significant negative consequences. These consequences include an increased risk of domestic violence, divorce, poverty, stunting in children, and cultural deviation. The phenomenon impacts the quality of life of individuals, family welfare, and societal development. Method: This descriptive study was conducted with 114 participants, who were surveyed using a random sampling technique. The survey targeted 101 households in Pappalluang Village. Data were collected through interviews to gather insights on the prevalence of early marriage in the village. Findings: The study revealed that early marriage is highly prevalent among teenagers in Pappalluang Village. The main factors contributing to early marriages include family pressure, economic challenges, a desire to preserve the family’s reputation, and local community traditions. Conclusion: Early marriage in Pappalluang Village is significantly influenced by social and cultural factors. Addressing the issues of family pressure, economic struggles, and traditions is crucial in reducing early marriages and their negative consequences on individuals, families, and the broader community. Novelty/Originality of this article: This study highlights the specific socio-cultural dynamics of early marriage in Pappalluang Village, offering unique insights into the interplay between family pressure, economic conditions, and local traditions. It provides a localized perspective that can inform targeted interventions in similar communities.